PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA PEGAWAI DIMEDIASI OLEH KOMITMEN KERJA PADA KOMISI PEMILIHAN UMUM PROVINSI SULAWESI TENGGARA - Nelni Nelni; Asrip Putera; Yusuf Montundu; Enny Wati (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to determine the effect of organizational culture and non-physical work environment on employee performance and to determine the influence of organizational culture and non-physical environment on work commitment. Determine the effect of work commitment on employee performance and examine the mediating effect of work commitment on the influence of organizational culture and non-physical work environment on employee performance. This research was conducted at the General Election Commission in Southeast Sulawesi Province. The population of this study were civil servants totaling 198 people. Determination of the sample using the Slovin formula so that the number of samples in this study was 132 civil servants. Data were collected using questionnaires and processed using analytical tools Structural Equational Modeling (SEM) AMOS.The results of this study indicate that organizational culture has no significant effect on employee performance. Organizational culture has a positive and significant effect on work commitment. The non-physical work environment has no significant effect on employee performance. The non-physical work environment has a positive and significant effect on work commitment. Work commitment has a positive and significant effect on employee performance. Work commitment mediates the influence of organizational culture on employee performance and the nature of the mediation is full mediation. Work commitment mediates the effect of the non-physical work environment on employee performance and the nature of the mediation is full mediation.